Dinâmica de transmissão da hanseníase em menores de 15 anos em área hiperendêmica na Região Norte do Brasil - FRANCO, Mariane Cordeiro Alves (Universidade Federal do Pará, 2017)
Leprosy, infectious and potentially crippling disease which, although curable, their diagnosis causes great psychosocial impact In Pará, Leprosy is maintained in an endemic form and the incidence in children under 15 years is worrying because it is the best indicator to assess their transferability. The objective was to describe the dynamics of transmission of leprosy in children under 15 years in hyperendemic area of North Region of Brazil, considering risk factors, territoriality and the spatial and temporal distribution of the disease from 2003 to 2013. Ecological and longitudinal series of cases study in the Village of Santo Antônio do Prata, municipal district of Igarapé Açu, state of Pará where it was analyzed the temporal pattern of leprosy cases, based on the detection of new cases and available in SINAN files of local health services in younger than 15 years old notified in the historical series from 2003 to 2013, emphasizing clinical, epidemiologic and geostatistical aspects. Were reported 226 leprosy cases in all age groups, 15.92% (36 cases) in younger than 15 years with a significant decline in detection rates in the studied decade. In the State of Pará there was a slight reduction of notifications. In the municipal district of Igarapé Açu occurred significant increase in the detection of new cases in the years 2005, 2009 and 2011, due campaigns in schools to identify skin lesions. The predominant age group was teenagers, independently of sex, confirming the long incubation period of the disease. Families have marked low educational and socioeconomic levels. Dermatologic changes that predominated was the unique lesion located in the lower limbs of paucibacillary, with identification of two MHV cases. Rates of treatment dropout and relapse are relevant, as well as the rate of disability presented among the cases, demonstrating the late diagnosis. Regarding factors of risk consanguinity and household contact factors were significantly relevant, with no differences among them and no difference in parental relationship The contact time was important, with an average of 8.6 years, and among the cases of children who had household contact with an index case, there was a high rate of absence of the second dose of BCG. Cases of leprosy in children under 15 when geocodified annually by area of community health agent and related with PB and MB total forms, were directly correlated with the multibacillary cases confirmed by positive Moran index (0.71) with a significant value and significance (0.019). Geostatistical analysis confirmed that, with indicators of classical epidemiology, cases of leprosy in children under 15 years are closely related to the multibacillary. We conclude that because leprosy is a disease that defies health vigilance in the Northern Region and at the State of Pará, Geostatistical resources added to the classical epidemiology resources allows better to understand the transmission dynamics and maintenance of the desease in hyperendemic areas. To Prevent the disease in children under 15 years in these areas is necessary to firmly act in vigilance of contacts in blood related and those who live close to MB cases.